Examining the Influences of Early Childhood Impulsivity and Intelligence on Global Functioning in Adolescence Among a Sample of High-Risk American Youth - Gajos, Jamie M. (Journal of developmental and life-course criminology, 2022)
Children’s impulse control and intelligence are important for health and social functioning later in life, but the degree to which they impact later outcomes via common vs. unique pathways is still unclear, particularly in high-risk samples. The Fragile Families and Child Wellbeing Study (n = 4,898; 48% female; 18% White) was used to examine the plausibility of common or “global” dimensions of health problems and antisocial behavior at approximately age 15, as well as to examine the possible roles of impulsivity and intelligence in their etiologies. To this end, we employed structural equation modeling, controlled for covariates, and leveraged ratings from parents, teachers, observers, and children. Findings suggest that childhood impulsivity forecasted higher levels on dimensions of health problems and antisocial behaviors in adolescence, whereas with impulsivity controlled, childhood intelligence forecasted greater general risk for age-typical antisocial behavior and did not significantly predict global health. Future studies aiming to elucidate the degree to which adolescent outcomes emerge via common pathways will benefit from the use of latent variable modeling.